Low-frequency 1f fluctuations in hydrodynamic and magnetohydrodynamic turbulence - Dmitruk, Pablo Ariel (2007)
We investigate the occurrence of 1f spectra of low-frequency fluctuations in numerical simulations of three-dimensional hydrodynamic and magnetohydrodynamic turbulence driven by a random forcing with a controlled correlation time. A range of one decade of 1f spectrum is observed when a strong background magnetic field is present. The frequency spectra of individual Fourier modes is also analyzed and it is observed that the 1f range is present in the largest available wavelength mode for the magnetohydrodynamic simulations with and without a background magnetic field and it is not observed (or is less clear) for the hydrodynamic case. The presence of 1f spectra of low-frequency fluctuations is also analyzed for two-dimensional magnetohydrodynamic and hydrodynamic turbulence simulations and it is observed in both cases. The origin of these long period fluctuations is discussed. © 2007 The American Physical Society.